Key Examine for Visit Intention on Gastronomy Tourism - Lu Man Hong; Woo Wai Yee (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
In recent decades, gastronomy tourism has increased in popularity among visitors and host countries, and it is now one of the most essential factors for travellers when choosing a location. Gastronomy tourism is now categorised as a niche market. The purpose of this research is to determine what factors impact visitors' decisions to visit Kelantan's culinary tourism. The relationship between the independent variables of meal pricing, food presentation, and ambiance, as well as the dependent variable of intention to visit, will be investigated in this study. This study used a quantitative technique, with 400 responses collected via an online questionnaire from people who had visited Kelantan at least once. Because 10 straight-lining replies were removed, 390 responses were submitted to smartpls data analysis. According to the findings, meal pricing, food presentation, and ambience have a direct impact on tourists' intentions to attend gastronomy tourism.